2016
DOI: 10.1007/s00775-016-1363-x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of CmlI, the arylamine oxygenase from the chloramphenicol biosynthetic pathway

Abstract: The diiron cluster-containing oxygenase CmlI catalyzes the conversion of the aromatic amine precursor of chloramphenicol to the nitroaromatic moiety of the active antibiotic. The X-ray crystal structures of the fully active, N-terminally truncated CmlIΔ33 in the chemically reduced Fe2+/Fe2+ state and a cis µ-1,2(η1:η1)-peroxo complex are presented. These structures allow comparison with the homologous arylamine oxygenase AurF as well as other types of diiron cluster-containing oxygenases. The structural model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 68 publications
0
69
3
Order By: Relevance
“…68, 81 The active site picture thus obtained for CmlI R in frozen solution from EXAFS analysis differs significantly from that derived from the crystal structure of CmlI 33 R . 39 For the latter, the hydroxo bridge observed in the EXAFS analysis is absent. Instead, there is a bidentate carboxylate bridge (E326) that gives rise to a longer Fe•••Fe distance of 3.6 Å.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…68, 81 The active site picture thus obtained for CmlI R in frozen solution from EXAFS analysis differs significantly from that derived from the crystal structure of CmlI 33 R . 39 For the latter, the hydroxo bridge observed in the EXAFS analysis is absent. Instead, there is a bidentate carboxylate bridge (E326) that gives rise to a longer Fe•••Fe distance of 3.6 Å.…”
Section: Resultsmentioning
confidence: 99%
“…5758 These assignments are based on metal-ligand distances found in the crystal structures of nonheme diiron proteins, 7, 7077 including diferrous CmlI. 39 The shorter Fe–N/O distance at 1.94 Å is assigned to a μ -hydroxo bridge based on comparison to the Fe–O distances associated with the μ -hydroxo ligand in the reduced clusters of CmlA 58 and synthetic ( μ -hydroxo)diferrous complexes. 7880 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…98,289,290 Optical, EPR, Mössbauer, and structural studies have demonstrated conclusively that CmlI, like AurF, contains a di-iron metallocofactor. Also similar to AurF, a combination of UV/Vis, Mössbauer, and resonance Raman spectroscopies have showed that the reaction of reduced Fe 2 II/II ClmI with O 2 generates a peroxo-Fe 2 III/III species ( 110 ) that has spectral properties distinct from those previously characterized in other non-heme di-iron enzymes.…”
Section: N–o Bond Forming Enzymesmentioning
confidence: 95%
“…The Mn(III)/ Mn(IV) center can be probed by MCD and the Fe(III) center by NRVS to correlate with the binuclear non-heme Fe enzymes [93]. Finally, a number of new biferrous enzyme classes are emerging (deoxyhypusine hydroxylase (DOHH) [94, 131], urease [95], CmlI [132], etc.) that are accessible to the VTVH MCD/DFT approach presented above to extend Table 1 and develop additional structure/function correlations.…”
Section: Concluding Commentsmentioning
confidence: 99%